Лексико-фразеологічна основа малої прози Агатангела Кримського у дзеркалі мовно-культурної ідентичності - Бибик, С. (Культура слова, 2021)
У статті запропоновано аналіз мови малої прози Агатангела Кримського з погляду відображення в ній лексико-фразеологічних складників мовно-культурної ідентичості. Виокремлено п’ять напрямків аналізу мовного матеріалу: за фразеологічним складом, за особливостями синоніміки, за графічно
виокремленими (залапкованими) лексемами, за соціостилістичними маркерами слововживання, за лексичними ознаками
індивідуально-авторської мовної норми.
Зроблено висновок про виражені в мові творів письменника
ознаки орієнтації на розмовний натуралізм, на змішування елементів різних ареалів побутування української мови, почасти –
на стилізацію мови представників певних соціальних типів, на
популяризацію самоцінності української розмовно-побутової і
окнижненої практики спілкування.
Простежено за методикою «слово у тексті і в словникові» особливості авторського слововживання, індивідуально-авторські пріоритети у виборі варіантів із рядів лексико-фразеологічних синонімів. The article offers an analysis of the language of short prose
by Ahatanhel Krymskyi in terms of reflecting the lexical and
phraseological components of linguistic and cultural identity. There
are five directions of analysis of language material: by phraseological
composition, by features of synonymy, by graphically separated
(patched) tokens, by socio-stylistic markers of word usage, by
lexical features of individual-authorial language norm.
The conclusion is made about the signs of orientation in the
language of the writer’s works on conversational naturalism, on
mixing elements of different areas of Ukrainian language, partly
on stylization of language of representatives of certain social types,
on popularization of self-worth of Ukrainian colloquial and literary
communication practice.
The peculiarities of the author’s word usage, individual-author
priorities in the choice of variants from the series of lexicalphraseological
synonyms are traced according to the method “word
in the text and in the dictionary”.
The question of linguistic and cultural identity through the
stylistics of lexical and phraseological units manifests itself as a
ratio of book and conversational, new and established, language
practice and social spheres of its existence.
The verbal palette of the Krymskyi’s prose writer should be
perceived as a portrait of time, as a socio-cultural slice with the
characteristic features of the norm of the Ukrainian literary
language (this is one area of linguistic and cultural assessment). The
writer’s artistic and fiction practice became a kind of experimental
platform, which testified to the potential properties of the general
literary and stylistic norm, which served to expand the lexical and
phraseological base of the Ukrainian language and revealed the
specifics of idiostyle (this is the second direction of linguistic and
cultural assessment).